Efeito dos fatores bióticos, ruídos e distância em espécies de aves no meio urbano de Caldas Novas-GO - (:unkn) unknown (Universidade Estadual de Goiás, 2021)
The advance in the occupation of the environment, the pressure on natural resources resulting from socioeconomic development and the advance in the urbanization process have drastically altered the biogeographic scenario, fragmenting habitats and interfering in the natural ecological dynamism. The present study aimed to evaluate the influence of environmental variables, plant richness and abiotic factors on the bird community in riparian forest areas. The work was developed along the Caldas Novas stream, where 16 points were chosen for sampling the avifauna, 13 in urban environments and three located in the Parque Estadual da Serra de Caldas Novas (PESCaN). Data were collected in the field in the years 2019 and 2020, using the method of observation by fixed point without sampling radius for birds and rapid survey by walking through vegetation. Records were made through audible and/or visual contact in a standard time frame of 15 min per point/sample for birds and for vegetation with on-site identification or, later, by recorded photos. In addition, at each point we collected data on environmental attributes: variables of human influence (garbage disposal, anthropization, presence of debris, deforestation, and sewage disposal), canopy cover, width of Permanent Preservation Areas (APP), and width of the watercourse. A total of 123 bird species and 117 plant species were recorded. Plant richness and exotic bird richness had a positive influence on the richness of birds using the forest environment. Noise intensity was an environmental factor that negatively influenced bird richness in general and birds using the forest environment. Bird richness did not change as the distance of the sampling points from the PESCaN increased, but the species composition of birds changed, with points closer together showing greater similarity in species composition. It was evident that the urban environment can support considerable richness of bird species, but the process of anthropization causes changes in the species composition of this environment, which starts to present a greater amount of generalist and exotic bird species. Thus, improving the protection and conservation of urban riparian forests is important to minimize the impacts of anthropization and improve conditions for the maintenance of local avifauna.
Título em outro idioma: effect of biotic factors noise, and distance on bird species in the urban environment of Caldas Novas-GO
Keywords: Conservação; Composição de espécies; Urbanização; Conservation; Species composition; Urbanization; CIENCIAS AGRARIAS